PERAN PSIKOLOGI DALAM MENINGKATKAN KUALITAS KERJASAMA TIM - Wahyunnisa Aisy Agustini; Anniez Rachmawati Musslifah; Faqih Purnomosidi (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to explore how psychology can be used to overcome barriers to teamwork and improve overall organizational performance. Teamwork is an important element in various contexts, from the business world to academic and social environments. Effective teamwork not only contributes to achieving common goals but also strengthens interpersonal relationships, increases job satisfaction, and optimizes productivity. Through a qualitative research approach and data collection from various literature sources, this article presents an in-depth analysis of the role of psychology in improving the quality of teamwork. The results of this research show that psychology has an important role in improving the quality of teamwork and has a significant influence. By understanding and overcoming obstacles in group dynamics, developing effective communication skills, and promoting coordination, balance of contribution, mutual support, effort, and cohesion in teams, psychology can assist in creating a work environment that is conducive to successfully achieving shared goals.